Identifikasi, Penilaian dan Pengendalian Risiko Kecelakaan Kerja dengan Metode HIRARC di PT ABC - Fatkur Rahman; Dene Herwanto (Peneliti.net, 2022)
PT ABC is one of the companies engaged in logistics with a high potential for work accidents as a result of the many types of raw materials stored, such as chemical raw materials, as well as the use of heavy equipment such as forklifts and storage of goods on high shelves. Several work-related accidents have occurred in the warehouse area which resulted in injury to workers or damage to equipment, such as collisions with tools or goods and fires due to electrical short circuits. In addition, several other risks also occur, such as low back pain caused by manual lifting of goods, damage to walls or buildings due to being bumped or hit by a forklift. This study aims to determine how high the level of work accidents at PT ABC is and how prevention needs to be done to avoid these accidents. The method used in this research is Hazard Identification Risk Assessment and Risk Control (HIRARC) to find out how high the level of work hazard or accident is. The results of this study indicate that there are 10 potential work accidents at PT ABC, where the process of moving goods and stuffing is a job that has the highest rate of work accidents.